A Study on the Infrastructure Service Satisfaction Index in Batu Bara Regency - Rizki Mazia Hakiki Rambe; Cut Nuraini; Abdi Sugiarto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This research aims to study the Infrastructure Service Satisfaction Index in Batu Bara Regency. The type of research employed in this study is qualitative research. Data collection techniques refer to the methods used to obtain the necessary data and information to achieve the research objectives. Data analysis is the process of processing data obtained from interviews, field notes, and documentation into new information, making the characteristics of the data easier to understand and useful for solving problems, particularly those related to the research. In this case, the researcher employs several data analysis techniques, namely: Data Reduction, Data Presentation, and Verification. The research results indicate that, in general, the level of public satisfaction with infrastructure development in Batu Bara Regency remains low. The community perceives that there is still an imbalance between villages in the development of road infrastructure and other village facilities, and they also feel that the performance of the Batu Bara Regency government is not optimal and is considered slow. The level of community participation in Batu Bara Regency in infrastructure development can be considered good and helps facilitate the infrastructure development process. Community participation includes providing suggestions or proposals, contributing labor such as mutual assistance, as well as donations of funds and materials. There are even some community members who participate by voicing dissatisfaction and not providing support.